Antimicrobial ethicists: Making ethics explicit in antimicrobial stewardship - Christina F. Yen; James B. Cutrell (Cambridge University Press, 2021)
Antimicrobial prescribing and the associated discipline of antimicrobial stewardship have inherent ethical and moral dimensions. We contend that the explicit, formal application of ethical principles and frameworks can strengthen and further justify the value of antimicrobial stewardship programs and their work. To illustrate the value of this process, we highlight 3 ethical scenarios that antimicrobial stewardship programs regularly encounter at the prescriber, institutional, and societal levels, and we analyze these scenarios using the Beauchamp and Childress biomedical ethics framework.